2019
DOI: 10.37757/mr2019.v21.n2-3.7
|View full text |Cite
|
Sign up to set email alerts
|

The Chronic Kidney Disease Epidemic in El Salvador: A Cross-Sectional Study

Abstract: INTRODUCTION Chronic kidney disease has reached epidemic levels in several Central American countries since the early years of this century. In El Salvador, it is the second cause of death in men, the fi fth in persons over 18 years old and the third cause of hospital deaths in the adult population. Its features, especially those of a subtype unassociated with traditional risk factors such as diabetes and high blood pressure, are only partially understood.OBJECTIVE Estimate the magnitude of chronic kidney dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
7
0
3
Order By: Relevance
“…In El Salvador, CKD is the second cause of death in men and the fifth in persons more than 18 years old. Death ascribed to kidney disease increased by 153% between 1997 and 2012 [10 ▪ ,11,12]. A kidney health research team found an 18% prevalence of CKD in Bajo Lempa, Usulután in 2009 [13].…”
Section: Coastal Plains Of El Salvador and Nicaraguamentioning
confidence: 99%
“…In El Salvador, CKD is the second cause of death in men and the fifth in persons more than 18 years old. Death ascribed to kidney disease increased by 153% between 1997 and 2012 [10 ▪ ,11,12]. A kidney health research team found an 18% prevalence of CKD in Bajo Lempa, Usulután in 2009 [13].…”
Section: Coastal Plains Of El Salvador and Nicaraguamentioning
confidence: 99%
“…Desde finales del siglo XX, se viene constatando la trágica irrupción de una dolencia que ha alcanzado proporciones epidémicas y que se ensaña en hombres jóvenes de comunidades agrícolas de Nicaragua y El Salvador, la ERC [13]. Para por lo menos un tercio de las decenas de miles de afectados por ERC, puede descartarse que las causas sean las que típicamente determinan el daño renal crónico: hipertensión y diabetes [14]. Esta modalidad epidémica ha sido bautizada de varios modos, especialmente como Enfermedad Renal Crónica de Causas no Tradicionales (ERCnT) [15].…”
Section: La Epidemia De Enfermedad Renal Crónica (Erc)unclassified
“…5,6 In Nicaragua, kidney disease–related mortality as high as 70/100,000 population has been reported, and the overall mortality is 12-fold higher than in the United States and Cuba, 7,8 whereas in El Salvador, CKD is the second leading cause of death in men, and overall kidney disease–related mortality is nine-fold higher than in the United States and Cuba. 7,9 CINAC prevalence in some regions of Sri Lanka is 6%–14.4% in men and 3.7%–17% in women, with higher prevalence of severe CKD in men. 10,11 The lack of kidney failure care in endemic areas has resulted in marked morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%